Acute Effects of Aerobic Exercise on Affect and Smoking Craving in the Weeks Before and After a Cessation Attempt. Issue 5 (15th May 2017) - Abrantes, Ana M; Farris, Samantha G; Minami, Haruka; Strong, David R; Riebe, Deborah; Brown, Richard A
Abstract: Introduction: Aerobic exercise may improve smoking abstinence via reductions in craving and negative affect and increases in positive moods. Acute changes in craving and affect before and after structured exercise sessions have not been examined during the weeks prior to and following quit attempts nor has smoking status been examined in relation to these effects. Given that regular cigarette smoking can be perceived as affect enhancing and craving reducing, it is not known whether exercise could contribute additional affective benefit beyond these effects. Method: Participants ( N = 57; 68.4% women) were low-active daily smokers randomized to cessation treatments plus either group-based aerobic exercise (AE) or a health-education control (HEC). Mood, anxiety, and craving were assessed before and after each intervention session for each of the 12 weeks. Carbon monoxide (CO) breath samples ≤ 5ppm indicated smoking abstinence. Results: During the prequit sessions, significantly greater decreases in anxiety following AE sessions relative to HEC sessions were observed. Changes in mood and craving were similar after AE and HEC sessions prior to quitting. Postquit attempt, significant reductions in craving and anxiety were observed after AE sessions but not following HEC. During the postquit period, positive mood increased following AE sessions relative to HEC only among individuals who were abstinence on that day. Conclusions: AE may be effective in acutely reducing anxiety prior to a quit attempt and both anxiety and craving following the quit attempt regardless of abstinence status. The mood-enhancing effects of AE may occur only in the context of smoking abstinence. Implications: The current findings underscore the importance of examining the acute effects of aerobic exercise prior to and after a cessation attempt and as a function of smoking status. Given the equivocal results from previous studies on the efficacy of exercise for smoking cessation, increasing our understanding of how aerobic exercise produces its reinforcing benefits for smokers attempting to quit could potentially inform the refinement (e.g., timing/sequencing) of exercise interventions within smoking cessation programs.